2001
DOI: 10.1086/501928
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cepaciaLower Respiratory Tract Infection Associated With Exposure to a Respiratory Therapist

Abstract: B. cepacia probably was transmitted among patients through use of extrinsically contaminated multidose albuterol vials. Respiratory therapy departments must pay close attention to infection control practices, particularly among new or temporary staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…342,343 Many healthcareassociated outbreaks of Burkholderia infections associated with contaminated skin antiseptics, mouthwashes, ultrasound gels, medications, and medical devices have been described. [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362] Other products that have become contaminated during use include nasal irrigation bottles contaminated with P. aeruginosa, 363,364 multiuse albuterol vials contaminated with B. cepacia, 348,357 acupuncture devices disinfected with glutaraldehyde contaminated with M. abscessus, 365 cosmetic surgical supplies contaminated with mycobacterial spp., and supplies used for liposuction. 366 Outbreaks of Achromobacter spp.…”
Section: Iiid2 Healthcare Sources: Water Surfaces Equipment Airmentioning
confidence: 99%
See 1 more Smart Citation
“…342,343 Many healthcareassociated outbreaks of Burkholderia infections associated with contaminated skin antiseptics, mouthwashes, ultrasound gels, medications, and medical devices have been described. [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362] Other products that have become contaminated during use include nasal irrigation bottles contaminated with P. aeruginosa, 363,364 multiuse albuterol vials contaminated with B. cepacia, 348,357 acupuncture devices disinfected with glutaraldehyde contaminated with M. abscessus, 365 cosmetic surgical supplies contaminated with mycobacterial spp., and supplies used for liposuction. 366 Outbreaks of Achromobacter spp.…”
Section: Iiid2 Healthcare Sources: Water Surfaces Equipment Airmentioning
confidence: 99%
“…(2) Proper training of personnel responsible for reprocessing equipment is important, including demonstration of competency initially and then at least annually, as is consistent adherence to reprocessing guidelines. 421 (3) Single-dose medication vials are always preferred, due to the risk of contamination 349,357,422,423 (if multidose medication vials must be used, then the manufacturer's directions for handling, dispensing, and storing must be followed precisely to prevent contamination and the transmission of potential pathogens). (4) Tap water may be used for cleaning nebulizers and other respiratory therapy equipment, but sterile water or water processed by filtration (filter size of less than or equal to 0.2 microns) must be used in the final rinse because tap water and distilled water may be contaminated with CF pathogens.…”
Section: Ive2 Healthcare Facilities: Respiratory Therapy Nebulizementioning
confidence: 99%
“…Aerosol-producing devices (e.g., nebulizers) may contain bacteria that can be aerosolized during use. In non-CF patients, health care-associated pneumonia has resulted from bacterial contamination of multidose medications vials due to aerosols generated by in-line and hand-held low-volume nebulizers (82,130,160,176; A. Crespo, P. Axelrod, K. St. John, K. Micklow, S. Alexander, F. Austan, P. Samuel, J. Arentzen, and A. Truant, Proc. 12th Annu.…”
Section: Care Of Respiratory Therapy Equipmentmentioning
confidence: 99%
“…P. cepacia was firstly described by Burkholder in 1950 [26]. Ramsey et al [27] recorded that bacteria belonging to the genera Burkholderia are recognized as pathogenic in fish, however Kayis et al [28] reported that Burkholderia cepacia was isolated from rainbow trout fish farms in Turkey (2006-2008) but was not a fish pathogen.…”
Section: Introductionmentioning
confidence: 99%